Self-nanoemulsifying delivery of andrographolide: ameliorating islet beta cells and inhibiting adipocyte differentiation - Syukri, Yandi; Bakhtiar, M. Taher; Martien, Ronny; Lukitaningsih, Endang; Nugroho, Agung Endo; Zakaria, Zainul Amiruddin (TUOMS Press, 2021)
Purpose: Insulin resistance is a characteristic of non-insulin-dependent diabetes mellitus associated with obesity and caused by the failure of pancreatic beta cells to secrete sufficient amount of insulin. Andrographolide (AND) improves beta-cell reconstruction and inhibits fat- cell formation. This research aimed to improve the delivery of water-insoluble AND in self- nanoemulsifying (ASNE) formulation, tested in streptozotocin (STZ)-induced diabetic rats and 3T3-L1 preadipocyte cells. Methods: A conventional formulation of AND in suspension was used as a control. The experimental rats were orally administered with self-nanoemulsifying (SNE) and suspension of AND for 8 days. Measurements were performed to evaluate blood glucose levels in preprandial and postprandial conditions. Immunohistochemistry was used to assess the process of islet beta cell reconstruction. In vitro study was performed using cell viability and adipocyte differentiation assay to determine the delivery of AND in the formulation. Results: ASNE lowered blood glucose levels (day 4) faster than AND suspension (day 6). The histological testing showed that ASNE could regenerate pancreatic beta cells. Therefore, ASNE ameliorated pancreatic beta cells. The in vitro evaluation indicated the inhibition of adipocyte differentiation by both AND and ASNE, which occurred in a time-dependent manner. ASNE formulation had better delivery than AND. Conclusion: ASNE could improve the antidiabetic activity by lowering blood glucose levels, enhancing pancreatic beta cells, and inhibiting lipid formation in adipocyte cells.